SLC38A10 Transporter Plays a Role in Cell Survival Under Oxidative Stress and Glutamate Toxicity - Tripathi, Rekha; Aggarwal, Tanya; Fredriksson, Robert (Frontiers in Molecular Biosciences, 2021)
Solute carrier (SLC) transporters regulate amino acids, glucose, ions, and metabolites that flow across cell membranes. In the brain, SLCs are the key regulators of neurotransmission, in particular, the glutamate/GABA-glutamine (GGG) cycle. Genetic mutations in SLCs are associated with various neurodevelopmental and neurodegenerative diseases. In this study, we have investigated the role of SLC38A10 under acute oxidative and glutamate stress in mouse primary cortical cells from SLC38A10 knockout (KO) mice. The ER/golgi localized transporter, SLC38A10, transports glutamate, glutamine, and alanine in brain cells, and the aim of this study was to determine the possible effects of removal of SLC38A10 in primary cortical cells under glutamate and oxidative challenges. Primary cortical neuronal cultures of wild-type (WT) cell and SLC38A10 KO mice were subjected to different concentrations of glutamate and hydrogen peroxide. There was no morphological change observed between KO and WT cortical neurons in culture. Interestingly, KO cells showed significantly lower cell viability and higher cell death compared to WT cells under both glutamate and hydrogen peroxide exposure. Further, we evaluated the possible role of p53 in neuronal cell apoptosis in KO cells. We found decreased intracellular p53 protein levels under glutamate and hydrogen peroxide treatment in KO cortical cells. In contrast, caspase 3/7 activity remains unaltered under all conditions. These results demonstrate an indirect relationship between the expression of SLC38A10 and p53 and a role in the cell defense mechanism against neurotoxicity.